Analisis Kesesuaian Lokasi Budidaya Rumput Laut dalam Meningkatkan Produksi di Desa Kumul Kecamatan Aru Utara Timur Batuley - Gainaugasiray, Aksamina J.; Tuhumury, Semuel F.; Pattinasarany, Mauren M. (Indonesian Journal of Sustainable Aquaculture, 2024)
The waters in Kumul Village are quite clear with rocky bottom conditions and little mud, so it is rich in potential fisheries and communities. Problems that occur in this village include land use conflicts, socio-economic and cultural issues, technology and aspects of cultivation land suitability. The problems faced by farmers from various dimensions require integrated aquaculture management in order to realize targeted and sustainable policies. One of the aspects looked at is the evaluation of aquatic ecological parameters by measuring physical and chemical parameters of the waters. The results of measurements at six research stations starting from April to May 2023 showed that the average temperature range of Kumul Village waters in the East North Aru District of Batuley was in the range of 27.57-28.20°C. DO content 9.47- 11.96 mg/L, pH 7.63-8.37, Salinity 24.45-25.39 ppt, Chlorophyll-a 1.67-2.96 mg/m3, Nitrate 0.11-0.16 mg/L, Phosphate 0.018-0.057 mg/L, Current speed 0.03-0.65 cm/s, Depth 1.55-4.97 m and Turbidity is in the range of 2.26-6.27 FTU. The condition of seawater in Kumul village, Aru Utara Timur sub-district, Batuley has excellent resource potential. The calculation of the carrying capacity of cultivated land obtained the following results the overall area of suitability is 9,243 consisting of St.1 very suitable covering 21.60 Ha, St.2 suitable covering 69.54 Ha and St.3 not suitable covering 1.29 Ha.